PERANAN NOTARIS DALAM PEMBUATAN AKTA WARIS TERHADAP ANAK LUAR KAWIN PASCA PUTUSAN MK NO.46/PUU-VIII/2010 - , LYDIA AMELIA, Dr. Sutanto, S.H., M.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aims of research is to know the Notary the role of notary within children beneficiary heritance and to know the number of inheritance of external married Pasca-Decision MK NO.46/PUU-VIII/2010. The research is normative law by using qualitative juridical analysis and primary of law, secondary law and tarsier law. The instrument to collect the data uses documentary and literatures. Meanwhile the research is classified into three parts by preparation, actuating, reporting of writing. The result of research was found that first the role of notary to make inheritance certificated of external married of children pasca putusan MK No. 46/PUU-VIII/2010, which found the fact the certificated stated by children of external married as heir of male which related biological with parents and the number of inheritance obtained by children of external married. Second, the number of inheritance of external married Pasca-Decision MK NO.46/PUU- VIII/2010 was similarity with children of external married which confession by parents as arranging KUHPerdata based on interpret of analogical.